ANALYSIS OF ILLICIT DRUGS AND NICOTINE IN A BUCCAL TOBACCO BRAND MARKETED IN YEMEN - AM THABIT, ANES; AL-GHANI, AHMED MS (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objectives: The objective of the present study was to check the potential presence of illicit drugs and to quantify the amount of nicotine in a buccal tobacco brand that had been observed to be increasingly used by Yemeni youths, since 2014, causing narcosis resembling states among them. Methods: Thin-layer chromatography (TLC) described by the United Nations Office on Drugs and Crime (UNODC) was used to screen illicit drugs in the tested brand. The illicit drugs investigated included opiates, heroin, amphetamines, and cocaine. The TLC results were confirmed as recommended by the UNODC using color chemical tests. Identification and quantification of nicotine in the brand was carried out using an appropriate high-performance liquid chromatography (HPLC) system. Results: No illicit drug was found in the tested tobacco brand. On the other hand, it was found that the amount of nicotine in just a single dose (sachet) of the buccal brand was 17.67±0.901 mg, which was 3.53-fold greater than usual buccal dose of nicotine (5 mg). Conclusion: With the exception of cannabis, opioids, and hallucinogens that were not investigated in this study due to technical obstacles, other major illicit narcotic drugs are not found in the brand. The brand contains high amount of nicotine/sachet. However, knowing that the user may use more than one sachet of the brands a day, there is a great potential of nicotine overdosing due to intake of the brand. This may cause a narcosis resembling state called “Nesbitt’s paradox,” characterized by reducing neuronal activity of the user.